Influence of High, Disperse API Load on Properties along the Fused-Layer Modeling Process Chain of Solid Dosage Forms - Marius Tidau; Arno Kwade; Jan Henrik Finke (MDPI AG, 2019)
In order to cope with the increasing number of multimorbid patients due to demographic changes, individualized polypill solutions must be developed. One promising tool is fused layer modeling (FLM) of dosage forms with patient-specific dose combinations and release individualization. As there are few approaches reported that systematically investigate the influence of high disperse active pharmaceutical ingredient (API) loads in filaments needed for FLM, this was the focus for the present study. Different filaments based on polyethylene oxide and hypromellose (HPMC) with different loads of theophylline as model API (up to 50 wt.%) were extruded with a twin-screw extruder and printed to dosage forms. Along the process chain, the following parameters were investigated: particle size and shape of theophylline; mechanical properties, microstructure, mass and content uniformity of filaments as well as dosage forms and the theophylline release from selected dosage forms. Especially for HPMC, increasing theophylline load enhanced the flexural strength of filaments whilst the FLM accuracy decreased inducing defects in microstructure. Theophylline load had no significant effect on the dissolution profile of HPMC-based dosage forms. Therefore, a thorough analysis of particle-induced effects is necessary to correlate mechanical properties of filaments, printability, and the dosage-and-release profile adjustment.